EFEKTIVITAS ORGANISASI PUBLIK DALAM PELAYANAN MASYARAKAT BERBASIS ONLINE (STUDI KASUS DI DINAS ADMINISTRASI KEPENDUDUKAN DAN CATATAN SIPIL KOTA SURAKARTA): (CASE STUDY AT THE POPULATION ADMINISTRATION AND CIVIL REGISTR - Putra, Riszi Sanjaya; Pramono, Joko; Sugiyarti, Sri Riris (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2023)
The author took the title of research Effectiveness of Public Organizations in Online-Based Community Services by taking a case study at the Population Administration and Civil Registration Office of Surakarta City. This study specifically aims to analyze the effectiveness of the role of public organizations of the Surakarta City Population Administration and Civil Registration Office in carrying out services for making Identity Cards and changing Family Cards in Surakarta City. The method used in this study is qualitative by taking the research location at the Surakarta City Government Office in the Surakarta City Hall Population Administration and Civil Registration Service unit. The method of collecting data from this study is carried out by observation, interview and documentation. As for the data analysis technique used, namely by using qualitative analysis theory as proposed by Miles and Hubberman, namely qualitative data analysis techniques. Based on the results of the study, it can be concluded that research on the effectiveness of public organizations in online-based community services (case study at the Surakarta City Population Administration and Civil Registration Office) went well despite obstacles in several indicators that need to be improved in online file management services, namely the existence of 1 special container used to communicate and send files. Because at this time, the official application listed on the Appstore is still not functioning optimally. Because it can only be used for community registration.